Evaluating the Structural Equation Model for Explaining Students' Academic Motivation Based on Emotion Regulation With the Mediating Role of Academic Self-efficacy - Najme Sadat Haji Vosoogh; Jahanshir Tavakolizadeh; Majid Pakdaman (Gonabad University of Medical Sciences, 2022)
Background: Students' academic motivation is one of the essential factors for academic achievement and the growth of societies, which emphasizes the importance of examining academic motivation correlations. Therefore, this research aims to evaluate the structural equation model for explaining students' academic motivation based on emotion regulation with the mediating role of academic self-efficacy. Methods: This quantitative-correlational research was conducted using structural equations. The research population included all high school students (3057 people) in the seventh, eighth, and ninth grades in Gonabad Town, Iran in the academic year of 2019-2020. In this population, 1646 were girls and 1411 were boys. A total of 250 people were considered a sample group by the multistage cluster random sampling method based on the principles of structural equations modeling. After obtaining the informed consent letters, all participants completed the situational motivation scale (SIMS) developed by Sinclair & McInroy (1992), the Morgan-Jinks student efficacy scale (MJSES), the cognitive emotion regulation questionnaires of Garnowski et al. (2002), revised adult attachment scale (1990) developed by Collins and Reed, and the classroom environments questionnaire (Fraser, 1995). Next, the data were collected and analyzed through Pearson correlation methods and structural equations using the SPSS software, version 19, and AMOS software, version 20. Results: Academic self-efficacy (0.20) and emotion regulation (0.37) directly and significantly affected academic motivation. In addition, emotion regulation (0.53) had a direct and significant effect on academic self-efficacy. There was an indirect relationship between emotional regulation (0.24) and mediated academic self-efficacy on academic motivation (P<0.01). Conclusion: The emotional regulation model is a favorable fit for students' academic motivation with the mediating role of academic self-efficacy. Therefore, the awareness of teachers, parents, principals and other educational experts can improve students' academic motivation.